An Anatomy of a Priory Church - Nash, George (Archaeopress Limited, 2015)
Based on documentary evidence, the Priory Church of St Marys in Abergavenny has been a place of worship since the late 11th century; this book traces the archaeology, history and conservation of this most impressive building, delving deep into its anatomy.